2004
DOI: 10.1016/j.jmps.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A continuum treatment of growth in biological tissue: the coupling of mass transport and mechanics

Abstract: Growth (and resorption) of biological tissue is formulated in the continuum setting. The treatment is macroscopic, rather than cellular or sub-cellular. Certain assumptions that are central to classical continuum mechanics are revisited, the theory is reformulated, and consequences for balance laws and constitutive relations are deduced. The treatment incorporates multiple species. Sources and uxes of mass, and terms for momentum and energy transfer between species are introduced to enhance the classical balan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(112 citation statements)
references
References 31 publications
2
110
0
Order By: Relevance
“…Conversely, a number of classical studies have explored growth and remodeling of tissues modeledas solids (Skalaketal, 1982;Cowin, 1983;Rodriguez et al, 1994), with no explicit reference to chemical reactions. More recently, studies have combined mixture analysis with chemical reactions (Humphrey and Rajagopal, 2002;Klisch et al, 2003;Garikipati et al, 2004), though they have been applied in narrower contexts than presented here.…”
Section: Constitutive Restrictionsmentioning
confidence: 99%
“…Conversely, a number of classical studies have explored growth and remodeling of tissues modeledas solids (Skalaketal, 1982;Cowin, 1983;Rodriguez et al, 1994), with no explicit reference to chemical reactions. More recently, studies have combined mixture analysis with chemical reactions (Humphrey and Rajagopal, 2002;Klisch et al, 2003;Garikipati et al, 2004), though they have been applied in narrower contexts than presented here.…”
Section: Constitutive Restrictionsmentioning
confidence: 99%
“…However, the complex nature of the cell wall growth and existence of competing modelling methodologies for the growth of soft tissue, e.g. single phase modelling [39] [46][47][48], mixture theory [49] and modelling based on the concept of natural configuration [50], imply that there is no single approach which is superior to others in all aspects of modelling. Therefore, the present study focuses on single phase (solid) modelling and tries to present a general framework for modelling cell wall growth based on solid mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors used conserving A to solve various types of problems [14]. In recent work, Garikipati et al [15] used this algorithm to model growth in biological tissue. Bathe [13] showed that the conserving B algorithm, which is incoporated in the commercial FEM software ADINA 8.7, is able to solve a specific type of problems where the Newmark algorithm is unstable and does not conserve energy and momentum.…”
Section: Introductionmentioning
confidence: 99%